Insights on the capacity value of photovoltaics, community batteries and electric vehicles. (June 2021) - Schram, Wouter L.; Aghaie, Hamid; Lampropoulos, Ioannis; Sark, Wilfried G.J.H.M. van
Abstract: The Capacity Value Ratio (CVR), or the part of its capacity that a technology can supply during peak residual load hours, is an important concept in the context of future resource adequacy. Especially for distributed resources, this is still underexplored territory. In this research, we investigate the peak reduction potential on both the distribution and transmission system level for a community battery coupled with photovoltaic (PV) systems as well as for smart charging approaches of electric vehicles (EVs) and vehicle-to-grid (V2G) technology. On the distribution level, it is shown that batteries charged only with PV-generated electricity reduce the peak residual load by 14.6%, whereas grid-charged batteries can reduce peak residual load by 30.0%. It is also found that deploying V2G can result in a decrease of the peak residual load, despite the additional EV charging demand. On the transmission system level, it is found that the CVR of PV is only 0.6%, however, the CVR of a PV-charged community battery is 25.0% whereas a grid-charged battery can have a CVR of 47.0%. The approximation method used in this study generates similar results as reliability-based methods found in literature. Regarding EVs, we approximate the load shifting potential of EV smart charging at 78.5% and the CVR of V2G at 8.9%. This indicates EVs could play an important role in maintaining resource adequacy in the context of a phase-out of conventional power plants, given that this has priority in the optimization of EV charging. Highlights: The capacity value ratio (CVR) is determined for distributed resources. Batteries can substantially increase the capacity value of photovoltaic (PV) systems. Electric vehicles (EVs) have much potential for contribution to resource adequacy. Discharge time of batteries and minimum SoC of EVs are important moderating factors.